An insight into transcatheter aortic valve implantation—a perspective from multidetector‐computed tomography. Issue 7 (18th March 2013) - Rajani, Ronak; Brum, Roberta L.; Barden, Edward; Drake, Sarah; Preston, Rebecca L.; Carr‐White, Gerald; Chambers, John B.
<x xml:space="preserve">Abstract</x> Transcatheter aortic valve implantation (TAVI) has now become an acceptable alternative to surgical aortic valve replacement for patients with severe aortic stenosis at high risk. The early enthusiasm for this technology has not diminished but rather has developed at an unprecedented rate over the last decade. Alongside the developments in implantation technique, transcatheter design, and postprocedural care, cardiac imaging modalities have also had to concurrently evolve to meet the perpetual demand for lower peri‐ and postprocedural complication rates. Although transthoracic and transesophageal echocardiography remain vital in patient's selection and periprocedural guidance, there is now emerging evidence that indicates that multidetector‐computed tomography (MDCT) may also have an equally important role to play. The aim of the current review is to examine the modern role of MDCT in assessing patients with aortic stenosis being considered for TAVI. © 2012 Wiley Periodicals, Inc.